Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1103/physreva.92.043616
|View full text |Cite
|
Sign up to set email alerts
|

Few-boson processes in the presence of an attractive impurity under one-dimensional confinement

Abstract: We consider a few-boson system confined to one dimension with a single distinguishable particle of lesser mass. All particle interactions are modeled with δ functions, but due to the mass imbalance the problem is nonintegrable. Universal few-body binding energies, atom-dimer and atom-trimer scattering lengths, are all calculated in terms of two parameters, namely the mass ratio m L /m H , and ratio g HH /g HL of the δ-function couplings. We specifically identify the values of these ratios for which the atom-di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Apart from a few exceptions [34][35][36][37][38][39][40][41], it has commonly been assumed that particles of different kinds have the same mass and the main impact on properties of the system comes from an imbalance of the number of particles. However, recently it was shown that for particles confined in a harmonic trap, the mass difference between different fermionic components leads to their spatial separation if interactions are strong enough [42].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from a few exceptions [34][35][36][37][38][39][40][41], it has commonly been assumed that particles of different kinds have the same mass and the main impact on properties of the system comes from an imbalance of the number of particles. However, recently it was shown that for particles confined in a harmonic trap, the mass difference between different fermionic components leads to their spatial separation if interactions are strong enough [42].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility for experimental implementation of mass-imbalanced atomic systems has driven multiple recent analyses. For general masses with contact interactions in an equal-frequency harmonic trap there are no exact solutions, so most previous approaches have relied on approximation schemes and numerical methods [25][26][27][28][29][30][31][32]. In this article, we show that for hard-core interactions there exist families of unequal masses for which there are exact solutions for the ground state and all excited states.…”
mentioning
confidence: 93%
“…The domain is a simplex whose shape depends on the mass ratios. For three particles, the six ordering sectors are just arcs of a circles and every set of masses is therefore integrable arXiv:1704.01433v3 [quant-ph] 28 Aug 2017 by separation of variables. For four particles, the 24 ordering sectors are spherical triangles.…”
mentioning
confidence: 99%
“…In addition to being difficult to experimentally measure, molecule-molecule collisions are extremely challenging to model, and quantitative calculations remain impossible for most diatomic molecules, including bialkali molecules. Recent work has emphasized the high resonance density inherent to bialkali (and heavier) atom-molecule [63][64][65][88][89][90][91][92][93] and molecule-molecule [94][95][96] collisions, building on earlier research on molecules formed from lighter atoms [61,[97][98][99][100][101][102][103][104][105].…”
Section: Introductionmentioning
confidence: 99%